Patients’ Knowledge and Perception on Anaesthesiologist And Anaesthesia - Nanyan, Suhaila Binti; Johari, Mohamad Fariz Bin; Holid, Mohamad Nazrin Bin; Othman, Usamah Bin (IIUM Medical Journal Malaysia, 2018)
Introduction: Anaesthesiologists play vital roles in perioperative patients’ care and chronic pain management. However, not many patients are aware of the role of anaesthesiologists. We aimed to measure the level of patients’ knowledge regarding the role of anaesthesiologist and anaesthesia. Materials and Methods: This was a single-centred, questionnaire-based cross sectional study. The self administered questionnaire was divided into three parts that includes, i) sociodemographic characteristics, ii) knowledge regarding role of anaesthesiologist, iii) knowledge of anaesthesia. Respondents were selected among patients attending several specialist clinics at the International Islamic University Malaysia Medical Centre (IIUM MC). Results: Almost 64% of the selected patients had previous experience of anaesthesia. Majority of the patients (78%) knew that anaesthesiologist is a medical qualified doctor, but only 52.5% of them knew the role of anaesthesiologist in operation theatre. Fifty eight percents of patients realized the fact that anaesthesiologist is primarily responsible to ensures the well-being during operation, 45.1% knew the involvement of anaesthesiologist in case of emergency and in the intensive care unit, 46.7% in managing obstetrics pain, 39.3% in long-standing pain, 52.5% on the issue of pre-operative visits and post-operative recovery. Besides that, 72.1% were well-informed regarding fasting before operation, 59.8% realized that smoking may affect the anaesthesia and surgery, 86.1% knew where anaesthesia will be administered, 66.4% and 62.3% of respondents knew regarding the general and regional types of anaesthesia respectively. Seventy three percents of patients realize how general anaesthesia will be administered. Lastly, only 54.9% of patients had some knowledge regarding complications of anaesthesia. There were also not much impacts of previous exposure of anaesthesia on the level of their knowledge. Conclusion: Patients’ knowledge regarding the role of anaesthesiologist and anaesthesia were average and variable.